Research Progress in Fiber Bragg Grating-Based Ocean Temperature and Depth Sensors - Xinyu Zhao; Chenxi Wei; Lina Zeng; Li Sun; Zaijin Li; Hao Chen; Guojun Liu; Zhongliang Qiao; Yi Qu; Dongxin Xu; Lianhe Li; Lin Li (Sensors)
Fiber Bragg gratings (FBGs) are widely used in stress and temperature sensing due to their small size, light weight, high resistance to high temperatures, corrosion, electromagnetic interference, and low cost. In recent years, various structural enhancements and sensitization to FBGs have been explored to improve the performance of ocean temperature and depth sensors, thereby enhancing the accuracy and detection range of ocean temperature and depth data. This paper reviews advancements in temperature, pressure, and dual-parameter enhancement techniques for FBG-based sensors. Additionally, the advantages and disadvantages of each method are compared and analyzed, providing new directions for the application of FBG sensors in marine exploration.